Gaussia princeps luciferase: a bioluminescent substrate for oxidative protein folding. (18th July 2018) - Yu, Tiantian; Laird, Joanna R.; Prescher, Jennifer A.; Thorpe, Colin
Abstract: Gaussia princeps luciferase (GLuc) generates an intense burst of blue light when exposed to coelenterazine in the absence of ATP. Here we show that this 5‐disulfide containing enzyme can be used as a facile and convenient substrate for studies of oxidative protein folding. Reduced GLuc (rGLuc), with 10 free cysteine residues, is completely inactive as a luciferase but >60% bioluminescence activity, compared to controls, can be recovered using a range of oxidizing regimens in the absence of the exogenous shuffling activity of protein disulfide isomerase (PDI). The sulfhydryl oxidase QSOX1 can be assayed using rGLuc in a simple bioluminescence plate reader format. Similarly, low concentrations of rGLuc can be oxidized by millimolar levels of dehydroascorbate, hydrogen peroxide or much lower concentrations of sodium tetrathionate. The oxidative refolding of rGLuc in the presence of a range of glutathione redox buffers is only marginally accelerated by micromolar levels of PDI. This modest rate enhancement probably results from a relatively simple disulfide connectivity in native GLuc; reflecting two homologous domains each carrying two disulfide bonds with a single interdomain disulfide. When GLuc is reoxidized under denaturing conditions the resulting scrambled protein (sGLuc) can be used in a sensitive bioluminescence assay for reduced PDI in the absence of added exogenous thiols. Finally, the general facility by which rGLuc can recover bioluminescent activity in vitro provides a sensitive method for the assessment of inhibitors of oxidative protein folding.